PER-VAGINAL DELIVERY OF AN EXTERNAL HYDROCEPHALIC CALF IN A BUFFALO-A CASE REPORT - PANDEY, ANAND KUMAR; SINGH, GYAN; DUTT, RAVI; SUNDER, SHYAM; KUMAR, SANDEEP; KUMAR, RAKESH (The Indian Journal of Animal Reproduction, 2011)
A case of congenital external hydrocephalus in a Murrah buffalo calf and its successful therapeutic managementhas been reported.
Keywords: Hydrocephalus; congenital; dystocia; buffalo